Health commodities inventory management performance and associated challenges in selected public health facilities of South Gondar Zone, Amhara Region, North Central Ethiopia: A mixed-methods cross-sectional study - Zewdu Tessema; Tesfaye Tsigu; Zelalem Tilahun; Gashew Tessema; Ayenew Berhan; Eskinder Eshetu Ali (PLoS ONE, 2026)
Introduction In the healthcare system, the supply chain refers to the coordinated flow of physical and technical resources needed to deliver quality patient care while adhering to budget constraints. To achieve this, measuring inventory management performance is essential. This process involves evaluating the efficiency and effectiveness of activities against predefined standards using established indicators. Therefore, this study aimed to assess the inventory management performance of health facilities in the South Gondar Zone, Northcentral Ethiopia. Methods This study employed a facility-based cross-sectional study design with a concurrent mixed-methods approach. Eighteen health facilities, representing 30% of the 57 health facilities in the South Gondar Zone, were included in this study. Quantitative data were collected using structured tools and analyzed in Microsoft Excel. Meanwhile, qualitative data were gathered from expert interviews and thematically analyzed to identify the major challenges faced by these facilities. Results Emergency ordering was frequent, with 83.3% of facilities placing at least one emergency order in 2020–2021, increasing to 100% placing two or more orders in 2021–2022. Inventory record accuracy was suboptimal, with an average accuracy rate of 71.3% (±9.6), and only 16.7% of facilities maintained up-to-date stock cards. While reporting rates were high (98.2%), report completeness (52.8%) and accuracy (72.2%) remained inconsistent. Storage performance was inadequate, as only 16.7% of facilities met acceptable storage standards (≥80% of criteria), despite high compliance with vaccine cold-chain requirements (94.1%). Qualitative findings identified human resource constraints, limited training, weak data management systems, and inadequate infrastructure as key contributors to poor inventory performance. Conclusion The performance of inventory management for health commodities in the study health facilities is low. This is primarily due to a shortage of skilled personnel, insufficient management support and budget, a lack of ongoing professional training, poor record-keeping practices, inaccurate data quality, and inadequate storage conditions. This investigation discovered that the frequency of emergency orders is the most important indicator, and all responsible bodies should pay more attention to reducing it, in addition to implementing other sound inventory management operations to build a strong health care delivery system.